KEBIJAKAN DESENTRALISASI DAN IMPLEMENTASI OTONOMI DAERAH DI KALIMANTAN TIMUR - Tri Widodo W. Utomo, Awang Faroek Ishak dan (Pusjar SKPP Lembaga Administrasi Negara, 2010)
Decentralization is a perfect concept but it doesn’t always demonstrate its superiority in the implementation stage. Approximately 80% new autonomous regions in Indonesia are considered to be failed in implementing decentralization values. In order to achieve the expected outcomes, decentralization should be accompanied by appropriate preconditions such as careful planning, effective implementation, and sufficient capacity both in individual, institutional, and system level. In the context of East Kalimantan Province, decentralization is perceived as an opportunity to accelerate local development through broader authorities and wider financial resources. In other words, East Kalimantan Provincial Government is visioning decentralization as an instrument to run governance reform and, at the same time, as a precondition to better development processes. Besides, the implementation of decentralization in East Kalimantan Province is directed to produce a synergistic win-win relationship with the central government, not a kind of trade-off or zero-sum relationship. In that sense, East Kalimantan Provincial Government has formulated priority agendas on local development issues. These priorities would be combined with pillars of bureaucratic reform as key leverage and indicators to measure the progress of local development in the wide-decentralization era. Keywords: Desentralisasi, Otonomi Daerah, Kalimantan Timur